Gender differences in self-harm and drinking behaviors among high school students in Beijing, China - Chai-Quan Li; Jing-Shu Zhang; Shang Ma; Ruo-Ran Lv; Jia-Li Duan; Dong-Mei Luo; Xiao-Jin Yan; Ning Ma; Yi Song (BMC, 2020)
Abstract Background Self-harm and drinking are both serious problems in adolescents and many studies presented evidence of their association. However, gender differences in this association are seldom deeply discussed. Our study aimed to evaluate the prevalence of self-harm and explore its association with drinking behaviors by gender and investigate the extent to which the gender differences exist in the association between self-harm and drinking. Methods A total of 32,362 students in grades 7 to 12 in Beijing, China were anonymously surveyed and included in our study using two-stage, stratified probability proportion sampling. Self-harm, drinking behaviors and other basic information were obtained from an anonymous questionnaire. Demographic variables, self-harm and drinking behaviors were analyzed using the Chi-square test and the Gamma test between genders and the gender differences in this association were analyzed by Log-binomial regression. Results The total prevalence of self-harm was 13.7% with no significant gender difference (χ 2 =0.352, P = 0.553). The prevalence of self-harm in girls decreased with age (G = -0.163, P < 0.001). Self-harm was associated with drinking behaviors in both boys and girls. The Log-binomial regression demonstrated that girls in the 16-19 years old group were at lower risk of self-harm than girls in the 12-15 years old group while this association was weaker in boys (1.493 vs 1.128). The higher OR for self-harm was found among girls with early drinking experiences compared with boys (2.565 vs 1.863). Girls who had previously drunk (i.e. drunk at least once) (2.211 vs 1.636), were currently drinking (3.400 vs 2.122) and performed binge drinking (6.357 vs 3.924) were at greater risk of self-harm than boys. Conclusion Among high school students, self-harm has a significant positive association with drinking and girls with drinking behaviors are at higher risk of suffering self-harm. Identifying adolescents' drinking behaviors is of vital importance to self-harm prevention and special attention should be focused on younger girls.